Graphene-based strain sensor with sandwich structure and its application in bowel sounds monitoring. Issue 45 (12th October 2022) - Zhou, Min; Yu, Yin; Zhou, Yi; Song, Lihui; Wang, Siyi; Na, Di
Abstract : Combining medicine and materials science. First application of graphene strain sensors for monitoring bowel sounds Abstract : Surgery is one of the primary treatment modalities for gastrointestinal tumors but can lead to postoperative ileus (POI), which can aggravate pain and increase costs. The incidence of POI can be effectively reduced by monitoring bowel sounds to assist doctors in deciding the timing of transoral feeding. In this study, we prepared a flexible strain sensor based on a graphene composite material and tested the feasibility of sensor monitoring of bowel sounds using simultaneous stethoscope and sensor monitoring. We found that the time of hearing the bowel sounds (12.0–12.1 s) corresponded to the time of waveform change monitored by the sensor (12.036 s), and the sound tone magnitude corresponded to the waveform amplitude. This proves that the application of sensors to monitor bowel sounds is feasible, which opens up a new field for the application of graphene sensors and provides a new way for clinicians to judge the condition of the intestine.